The Indigenization of Christian Healthcare in China: The Case of Canton Hospital - TONG Meng, (Journal of Research for Christianity in China (JRCC), 2025)
This paper examines the historical transition of Canton Hospital into Lingnan University around 1930 based on primary archives such as its annual reports. It delves into the era's context and compares key aspects before and after this event—including patient volume, medical staff, funding sources, and religious activities—to reconstruct the hospital's process of becoming a truly independent institution.